2019
DOI: 10.1108/qaoa-06-2018-0026
|View full text |Cite
|
Sign up to set email alerts
|

The relation between social isolation and increasing suicide rates in the elderly

Abstract: Purpose Suicidal attempts and thoughts are particularly relevant to the health of the elderly and can impact not only the individual, but family, friends and spouses as well. This topic is important for the gerontological research community, particularly as it relates to social isolation and the feeling of loneliness, common in this population group. The purpose of this paper is to investigate new knowledge about the relationship between an increased risk of suicide in the elderly and social isolation or lonel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 19 publications
(43 reference statements)
1
12
0
1
Order By: Relevance
“…This explanation corresponds with empirical evidence, namely that divorced, separated, widowed, or persons who were never married are at higher risk of suicide mortality [ 20 , 39 ]. Other groups with less social integration and more isolation, such as the elderly [ 55 ], or those less engaged in religious practices [ 56 ], are also prone to suicide [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…This explanation corresponds with empirical evidence, namely that divorced, separated, widowed, or persons who were never married are at higher risk of suicide mortality [ 20 , 39 ]. Other groups with less social integration and more isolation, such as the elderly [ 55 ], or those less engaged in religious practices [ 56 ], are also prone to suicide [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has revealed the vulnerability of elderly people and the lack of social mechanisms to prevent their social isolation and unwanted loneliness as a result of the confinement. The perception of aging among the people over 65 years old is usually associated to loneliness [ 1 ], one of the most widespread and relevant issues among this age group along with social isolation [ 2 ]. The confinement has intensified this perception, becoming a public health concern [ 3 ] and drawing attention from media and governments [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research has found that suicide and suicidal ideation are another consequence of social isolation in the elderly (Heuser and Howe 2019;Hong 2017;Kwon et al 2018). Suicidal ideation can be especially prevalent in people who feel isolated after the death of a spouse in older age (Bock and Webber 1972).…”
Section: The Consequences Of Isolationmentioning
confidence: 99%